Sumber dan Penggunaan Modal Bisnis dalam Islam - Helina Y Pakaya; Sofhian Sofhian (Al-Buhuts, 2022)
This study aims to determine the sources and expenditures of capital in the perspective of Islamic business, while the method used is a qualitative method by collecting data from literature, books, journals and other scientific works that are relevant to the subject to be studied. Analysis of the sources and use of capital in Islamic business can basically come from all lines in the sense that it can be from personal funds or from other people who have attachments and the rules that are built must be in accordance with the breath of Islam as well as in its use must go through management that does not go out of the corridor of Islam. so that the results obtained are not in doubt so that whoever is involved in the business besides getting profit also gets blessings from Allah SWT.